2001
DOI: 10.1159/000056329
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of (–)-Epigallocatechin-3-Gallate on UVA- and UVB-Induced Skin Damage

Abstract: It has been known that green tea and its components possess significant chemopreventive effects against chemical carcinogens and photo-caused skin tumor formation. In this study, the protective effects of (–)-epigallocatechin-3-gallate (EGCG), a major green tea catechin, on the ultraviolet (UV)-induced skin damage (photoaging) were studied in guinea pigs, hairless mice and human dermal fibroblast cultures. The lipid peroxidation was significantly reduced in the EGCG-treated group. The amount of lipid peroxides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 30 publications
1
82
0
1
Order By: Relevance
“…The only previous study examining the effects of EGCG on UVA radiation reported its reduction of UVA-induced AP-1 and NF-KB transcription factor activities, 32 processes known to be affected by redox status 33,34 thus providing additional evidence for EGCG antioxidant action against UVA. Wei et al 15 also reported the protection afforded by a green tea fraction containing a number of polyphenols against UVA-induced oxidative damage but only in a DNA solution.…”
Section: Discussionmentioning
confidence: 99%
“…The only previous study examining the effects of EGCG on UVA radiation reported its reduction of UVA-induced AP-1 and NF-KB transcription factor activities, 32 processes known to be affected by redox status 33,34 thus providing additional evidence for EGCG antioxidant action against UVA. Wei et al 15 also reported the protection afforded by a green tea fraction containing a number of polyphenols against UVA-induced oxidative damage but only in a DNA solution.…”
Section: Discussionmentioning
confidence: 99%
“…This study also reveals that treatment of human fibroblasts in culture with EGCG blocked the UV-induced increase of collagen secretion and collagenase mRNA level, and also inhibited UV-induced nuclear transcription factors NF-jB and AP-1 binding activities. 118 These investigations suggest that green tea has a potential to decrease UV-induced oxidative stress and oxidative stress-mediated skin diseases in humans.…”
Section: Tea/green Teamentioning
confidence: 99%
“…24 Inhibition of UV-induced lipid peroxidation by EGCG is a characteristic feature, which may prevent human skin from solar UV light-induced basal cell and squamous cell carcinoma and premature aging of the skin. Kim et al 118 observed that EGCG treatment to guinea pig skin inhibits UVB-induced lipid peroxidation and skin photodamage. This study also reveals that treatment of human fibroblasts in culture with EGCG blocked the UV-induced increase of collagen secretion and collagenase mRNA level, and also inhibited UV-induced nuclear transcription factors NF-jB and AP-1 binding activities.…”
Section: Tea/green Teamentioning
confidence: 99%
“…Based on several in vitro and in vivo studies, polyphenols present in green tea, most notably its major constituent epigallocatechin-3-gallate (EGCG), have been shown to exert antioxidant activity and photochemopreventive effects (Elmets et al, 2001;Katiyar and Mukhtar, 2001;Katiyar et al, 2001a, b;Kim et al, 2001;Nomura et al, 2001;Afaq et al, 2003a). Previous cell culture studies from our laboratory have shown that EGCG inhibits UVBmediated phosphorylation of MAPKs (Katiyar et al, 2001a) and activation of NF-kB pathways in normal human epidermal keratinocytes (NHEK) (Afaq et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%